Hospital Admissions for Childhood Asthma After Smoke-Free Legislation in England - Millett, Christopher (Pediatrics, 2013)
OBJECTIVE: To assess whether the implementation of English smoke-free legislation in July 2007 was associated with a reduction in hospital admissions for childhood asthma. METHODS: Interrupted time series study using Hospital Episodes Statistics data from April 2002 to November 2010. Sample consisted of all children (aged ≤14 years) having an emergency hospital admission with a principle diagnosis of asthma. RESULTS: Before the implementation of the legislation, the admission rate for childhood asthma was increasing by 2.2% per year (adjusted rate ratio 1.02; 95% confidence interval [CI]: 1.02–1.03). After implementation of the legislation, there was a significant immediate change in the admission rate of −8.9% (adjusted rate ratio 0.91; 95% CI: 0.89–0.93) and change in time trend of −3.4% per year (adjusted rate ratio 0.97; 95% CI: 0.96–0.98). This change was equivalent to 6802 fewer hospital admissions in the first 3 years after implementation. There were similar reductions in asthma admission rates among children from different age, gender, and socioeconomic status groups and among those residing in urban and rural locations. CONCLUSIONS: These findings confirm those from a small number of previous studies suggesting that the well-documented population health benefits of comprehensive smoke-free legislation appear to extend to reducing hospital admissions for childhood asthma.